Evaluation of touch screen vibration accessibility for blind users - Awada, Amine (2013)
In this demo paper, we briefly present our experimental prototype, entitled EVIAC (EValuation of VIbration Accessibility), allowing visually impaired users to access simple contour-based images using vibrating touch screen technology. We provide an overview of the system's main functionalities and discuss some experimental results.